2013
DOI: 10.1152/jn.00533.2011
|View full text |Cite
|
Sign up to set email alerts
|

Roles of default-mode network and supplementary motor area in human vigilance performance: evidence from real-time fMRI

Abstract: We used real-time functional magnetic resonance imaging (fMRI) to determine which regions of the human brain have a role in vigilance as measured by reaction time (RT) to variably timed stimuli. We first identified brain regions where activation before stimulus presentation predicted RT. Slower RT was preceded by greater activation in the default-mode network, including lateral parietal, precuneus, and medial prefrontal cortices; faster RT was preceded by greater activation in the supplementary motor area (SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 41 publications
(43 reference statements)
6
63
0
1
Order By: Relevance
“…An interesting observation in this regard is that the balance between the neural activity of the SMA and the DMN has been shown to be of crucial importance in psychomotor response speed (Hinds et al, 2013). A lack of SMA activity before stimulus presentation is related to prolonged reaction time (Hinds et al, 2013). The strong negative relationship between DMN activity and SMA activity in depression observed in our study at resting state fits well with the important clinical symptoms of psychomotor retardation often seen in MDD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…An interesting observation in this regard is that the balance between the neural activity of the SMA and the DMN has been shown to be of crucial importance in psychomotor response speed (Hinds et al, 2013). A lack of SMA activity before stimulus presentation is related to prolonged reaction time (Hinds et al, 2013). The strong negative relationship between DMN activity and SMA activity in depression observed in our study at resting state fits well with the important clinical symptoms of psychomotor retardation often seen in MDD.…”
Section: Discussionsupporting
confidence: 81%
“…The SMA is thought to be involved in motor preparation and the initiation of movement. An interesting observation in this regard is that the balance between the neural activity of the SMA and the DMN has been shown to be of crucial importance in psychomotor response speed (Hinds et al, 2013). A lack of SMA activity before stimulus presentation is related to prolonged reaction time (Hinds et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/brain mechanisms may be shared between trial-by-trial IIV and IIV of iFC. It has been shown that DMN deactivation (Anticevic et al, 2010;Hinds et al, 2013) and strength of anticorrelation between DMN and task-positive networks (Kelly et al, 2008) are positively correlated with task performance. More general evidence suggests that intrinsic neuronal fluctuations captured in iFC are functionally relevant, impacting trial-by-trial variability of both BOLD and behavioral responses (Fox et al, 2006(Fox et al, , 2007Mennes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows estimation of the contribution of individual frequencies to the analysed signal ( Figure IB). In the case of cognitive electrophysiological research, frequencies are divided into spectral bands with distinct functional associations: delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13)(14), beta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (>30 Hz) ( Figure IC).…”
Section: Supervisory Systems Of Sustained Attentionmentioning
confidence: 99%